2013
DOI: 10.1179/1973947813y.0000000078
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and clinical effects: is the number what counts?

Abstract: Probiotics are defined as 'live microorganisms that when administered in adequate amounts confer health benefits on the host', underlining the need of microbial viability and the requirement of a suitable dose to obtain a health benefit. The dose and the administration regimen are critical issues for probiotics either ingested as foods claiming health benefits or used as drugs in clinics. In fact, regulatory authorities demand to guarantee consumers that a probiotic is effective in the recommended conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 153 publications
1
44
0
3
Order By: Relevance
“…During the 30 days of protocol, the fermented probiotic product showed more than 9 logCFU/g of the three organisms analyzed, which is considered appropriate for them to exert their probiotic effects [51,52]. …”
Section: Resultsmentioning
confidence: 99%
“…During the 30 days of protocol, the fermented probiotic product showed more than 9 logCFU/g of the three organisms analyzed, which is considered appropriate for them to exert their probiotic effects [51,52]. …”
Section: Resultsmentioning
confidence: 99%
“…A review by Bertazzoni et al 27 concluded that a probiotic treatment should be designed around the dose–effect relationships established in humans. In 2012, Mihatsch et al 28 systematically analysed the level of evidence in 15 published RCTs on probiotics in preterm infants and concluded that there was insufficient evidence to base a general recommendation for routine use of probiotics in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are defined as live microorganisms, which colonize the gut and promote benefits to host health [110,111,112,113,114,115]. Prebiotics can modulate the structure and metabolism of beneficial microbes in the colon and improve host health [116,117,118,119].…”
Section: Intestinal Microbiome Targeting Strategiesmentioning
confidence: 99%